Pilomatrixoma: a diagnostic pitfall on fine-needle aspiration cytology of benign ‘neck metastases’ - Asha'ari, Zamzil Amin; Shiyuti, Muhd Izani; Abdullah, Kahairi; Selimin, Arfahiza; Sathananthar, KS (Faculty of Medicine, International Islamic University Malaysia, 2014)
Pilomatrixoma is a benign tumour that originates from the matrix of the hair root. This rare tumour is usually managed by the dermatologists. The commonest location of this tumour is in the head and neck region; hence, it can be encountered by any doctors with interest in this area. When presented in the neck, this hard tumour may pose a diagnostic challenge. A case report of pilomatrixoma misdiagnosed as a metastatic neck disease from fine-needle aspiration cytology is presented. The mistake in the diagnosis has led to a more aggressive and high morbidity surgery than necessary. It is important that head and neck doctors be aware of this condition and includes it in the differential diagnosis of hard masses presenting in the neck.